Oil Exploration and Exploitation in Nigeria and the Challenge of Sustainable Development: An Assessment of the Niger Delta - Enyoghasim, Michael Oguwuike; Anochiwa, Lasbrey; Agbanike, F. Tobechi; Uwazie, Iyke Uwazie; Kalu, E. Uma; Onwuka, O. Kelvin; Okwor, Sunday Amalunweze; Ogbonnaya, Ikwor Okoroafor (International Journal of Energy Economics and Policy, 2019)
The study seeks to evaluate the environmental problems associated with oil exploration and exploitation in the Niger Delta area of Nigeria on one part with a focus on empirical examination of one of the variables highlighted in the literature - emission of CO2 on people’s health. With data 1980-2015 drawn from CBN bulletin, we employed OLS and 3SLS regression model to analyze. Life expectancy at birth is the dependent variable, while carbon emission, gross domestic product per capital, female education, and public health expenditure are explanatory variables. Findings show that Carbon emission (CO2EM) has a negative coefficient which is in line with the theoretical expectation. It is observable that an increase in carbon emission by one unit will reduce life expectancy by 0.04 per cent. This result supports the unsustainability of the business and gas emissions and oil spill in the Delta region as harmful to the wellbeing of the masses. Keywords: Carbon emission, Oil exploration, environmental degradation, resource curse, JEL Classifications: O13, Q33, Q34 DOI: https://doi.org/10.32479/ijeep.7812